2013
DOI: 10.1111/are.12158
|View full text |Cite
|
Sign up to set email alerts
|

Hatchery seed production of giant freshwater prawn,Macrobrachium rosenbergiiusing inland ground saline water in India

Abstract: The suitability of inland saline water (ISW) from the Lahli‐Baniyani Fish Farm, Rohtak was investigated for the larval rearing of giant freshwater prawn (GFP), Macrobrachium rosenbergii. Six experiments were conducted. In Experiment‐I, 54% of the larvae metamorphosed to postlarvae (PL) in constituted seawater (CSW) whereas total mortality occurred at larval stages (LS)‐II and LS‐III in ISW with salinity of 12 g L−1. Larvae survived to LS‐IV in Experiment‐II, when ISW was supplemented with K+~ SW. In Experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Rahman et al [3] have reported higher survival of P. monodon in ISW when the level of calcium was reduced from 921.8 mg/L to 200 mg/L at a salinity of 12.5 g/L. High level of calcium has also been found to impair the larval development in Macrobrachium rosenbergii [11]. Wurts and Stickney [29] have correlated the survival and mortality of red drum with calcium-sodium ratio, and recommended this to be closer to 0.038.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Rahman et al [3] have reported higher survival of P. monodon in ISW when the level of calcium was reduced from 921.8 mg/L to 200 mg/L at a salinity of 12.5 g/L. High level of calcium has also been found to impair the larval development in Macrobrachium rosenbergii [11]. Wurts and Stickney [29] have correlated the survival and mortality of red drum with calcium-sodium ratio, and recommended this to be closer to 0.038.…”
Section: Resultsmentioning
confidence: 99%
“…Wurts and Stickney [29] have correlated the survival and mortality of red drum with calcium-sodium ratio, and recommended this to be closer to 0.038. Raizada et al [11] and Zang et al [30] have given importance to Mg 2? /Ca 2?…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These production rates are lower than other prawn producing countries, such as China, India, Taiwan, Thailand and Vietnam (Weimin and Xianping 2002;Raizada et al 2005;Vicki 2007). It has reported that the present level of annual prawn production can be increased to 1500-2500 kg/ha/year through the application of advanced technologies (Katalyst 2009).…”
Section: Discussionmentioning
confidence: 90%